CHARACTERIZATION OF ACTIVATED CARBON AS AN ADSORBENTMEDIUM FOR CARBON DIOXIDE - Christabel, Vanessa
Biogas is an alternative energy source that can be used as a substitute for fuel. Animal waste is one of the issues in areas of Indonesia where people work as livestock farmers. Animal waste can be utilized as a raw material for biogas production and can be used as an alternative energy source. However, biogas has the drawback of having a relatively low calorific value due to its high CO2 content. Therefore, research on the characterization of activated carbon as a carbon dioxide adsorbent media is conducted to broaden the use of biogas, such as for natural gas and bio-CNG. The adsorption method is chosen because it is easy to implement on various production scales and requires relatively low energy. The characterization of activated carbon is carried out using the adsorption process in Thermogravimetric Analysis (TGA), which consists of heating up to 110°C with N2 flow, cooling down to 30°C with N2 flow, and CO2 adsorption conducted for up to 4 cycles. Experiments were conducted with variation in activated carbon particle sizes, namely 100/120 mesh and 200/230 mesh, as well as types of activated carbon, namely impregnated activated carbon and generic activated carbon. It was found that the adsorption capacities for KI 100/120, KI 200/230, KG 100/120, and KG 200/230 were respectively 25.2; 20.7; 10.9; and 8.9 mg CO2/g. The active surface areas for KI 100/120, KI 200/230, KG 100/120, and KG 200/230 were respectively 622.14; 624.63; 924.42; and 892.49 m2 /g. The 100/120 mesh activated carbon had a higher CO2 adsorption capacity compared to the 200/230 mesh size. Impregnated activated carbon was able to double the adsorption capacity. The adsorption kinetics for KI activated carbon was pseudo-second-order, while for KG activated carbon it was intraparticle diffusion.